A Comment on "Interregional Contact and the Formation of a Shared Identity" - Adrien Foutelet; Bo-Yeon Jang; María Medellín-Esguerra (Institute for Replication (I4R), 2025)
Bagues and Roth (2023) examine the effect of interregional contact induced by compulsory military service on sympathy towards people from other regions and the consolidation of a national identity in the context of Spain. They find that conscripts assigned away from their home region have 0.8 sd greater contact with people from other parts of the country and have 0.06 sd more positive emotions towards them. For conscripts hailing from regions with peripheral nationalistic movements, these effects are larger by 0.210- 0.318 sd and 0.03-0.04 sd respectively. In addition, soldiers from regions with separatist movements tend to have 0.262 sd greater identification with Spain after service, and all effects are statistically significant at the 5% and 10% levels. In this comment, we successfully verify that the paper is computationally reproducible and correct one minor coding error that does not affect the studies' conclusions. We further confirm the robustness of the main results to dropping all controls, excluding pilot survey observations, and controlling for age at military enrollment, with possible heterogeneity in later military years.
Keywords: 330